2022
DOI: 10.1177/17562848221104951
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal strictures in Crohn’s disease: a 2021 update

Abstract: Intestinal strictures remain one of the most intractable and common complications of Crohn’s disease (CD). Approximately 70% of CD patients will develop fibrotic strictures after 10 years of CD diagnosis. Since specific antifibrotic therapies are unavailable, endoscopic balloon dilation and surgery remain the mainstay treatments despite a high recurrence rate. Besides, there are no reliable methods for accurately evaluating intestinal fibrosis. This is largely due to the fact that the mechanisms of initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…Since fibrotic complications are a prominent feature of Crohn’s disease (CD) ( 2, 3 ) and recent data have shown that profibrotic activity of human lung fibroblasts is associated with downregulated KLF2, elevated CCN2 levels, and increased collagen production ( 13 ), we aimed to investigate whether intestinal fibroblasts in CD share similarities with this fibrotic phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since fibrotic complications are a prominent feature of Crohn’s disease (CD) ( 2, 3 ) and recent data have shown that profibrotic activity of human lung fibroblasts is associated with downregulated KLF2, elevated CCN2 levels, and increased collagen production ( 13 ), we aimed to investigate whether intestinal fibroblasts in CD share similarities with this fibrotic phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Crohn’s disease (CD) is characterized by chronic relapsing inflammation that, in contrast to ulcerative colitis (UC), may lead to intestinal fibrosis causing lifelong disabling illness with a large impact on the quality of life and the healthcare systems ( 1, 2 ). Therefore, understanding the mechanisms of initiation and propagation of intestinal fibrosis in CD is crucial to providing knowledge for diagnosis and better care of patients ( 3, 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…10 Intestinal strictures form part of the natural history of Crohn's disease and will occur in up to 70% of patients over a 10-year period. 11 The strictures are classified as inflammatory, fibrotic, primary, or anastomotic. 12 Inflammatory strictures result from edema of the intestinal lining, while fibrotic ones are caused by chronic inflammation that results in the accumulation of extracellular matrix and hyperproliferation of smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal strictures form part of the natural history of Crohn's disease and will occur in up to 70% of patients over a 10‐year period 11 . The strictures are classified as inflammatory, fibrotic, primary, or anastomotic 12 .…”
Section: Discussionmentioning
confidence: 99%
“…While a rectal stricture may represent residual tumor scar tissue, its formation may be increased by ICI-induced inflammation and colitis in and around the tumor bed. Similarly, strictures have been reported in patients diagnosed with inflammatory bowel disease (IBD) [ 53 , 54 ], which can be associated with an increased risk of severe GI adverse events [ 55 , 56 ] when treated with immune checkpoint inhibitors. The patient in our cases study had no prior history of IBD and in follow-up had no further symptoms of colitis.…”
Section: Response Assessment and Management Of Immunotherapy-related ...mentioning
confidence: 99%